Anti-influenza virus activity of the elenolic acid rich olive leaf ( L.) extract Isenolic - Aurora Salamanca (SAGE Publishing, 2021)
Seasonal flu is caused by influenza infection, a virus that spreads easily in human population with periodical epidemic outbreaks. The high mutational rate of influenza viruses leads to the emergence of strains resistant to the current treatments. Due to that, scientific research is focusing on the development of new anti-influenza agents as alternative or complementary treatments. Olive tree ( Olea europaea L.) has been a source of ancestral remedies due to its antimicrobial activity. Thus, the aim of this study was to test the anti-influenza activity of a standardized olive leaf extract rich in elenolic acid (EA), Isenolic ® , compared with oseltamivir. Isenolic ® extract was characterized by High Performance Liquid Chromatography (HPLC)-Mass Spectrometry and its content in EA was determined by HPLC. Cytotoxicity, viral neuraminidase inhibitor activity and cell viability protection against influenza infection of Isenolic ® were tested in vitro using sialic acid overexpressing Madin-Darby Canine Kidney cells. Isenolic ® formulations showed a 4% and 8% dry basis. Oseltamivir and Isenolic ® extracts showed anti-influenza activity. The 8% Isenolic ® formulation showed a dose-dependent neuraminidase inhibitor activity higher than the 4% formulation, and preserved cell viability under viral infection. Thus, Isenolic ® become a promising natural alternative to existing influenza treatments.